Efficacy of water skin decontamination in vivo in humans: A systematic review. Issue 3 (26th August 2021) - Kashetsky, Nadia; Law, Rebecca M.; Maibach, Howard I.
Abstract: With the constant possibility of occupational exposures, chemical warfare, and targeted attacks, increased attention has been given to determining effective and timely dermal decontamination strategies. This systematic review summarises experimental studies reporting decontamination with water‐based solutions of dermal chemical contaminants with in vivo human data. Embase, MEDLINE, PubMed, Web of Science, and Google Scholar databases were comprehensively searched using search terms ("cutaneous" or "skin" or "dermal" or "percutaneous") and ("decontamination" or "decontaminant" or "skin decontamination") to include 10 studies, representing 18 chemical contaminants, 199 participants, and 351 decontamination outcomes. Three studies included data from decontamination with water (10.8%, n = 38/351 decontamination outcomes), seven with soap and water (68.4%, n = 240/351 decontamination outcomes), and two with 10% isopropanol distilled water (20.8%, n = 73/351 decontamination outcomes). Results of dermal decontamination using water showed complete decontamination (CD) outcomes in 52.6% ( n = 20/38) and partial decontamination (PD) in 47.4% ( n = 18/38); using soap and water showed PD outcomes in 92.9% ( n = 223/240) and minimal to no effect in 7.1% ( n = 17/240); and using 10% isopropanol distilled water achieved PD outcomes in 100.0% ( n = 73/73). Available data show that decontamination with water, soap and water, and 10% isopropanol distilled water is incomplete. Much remains to be learned about decontamination of the large variety of chemical contaminants including a range of molecular weights, lipid and water solubilities, melting points, volatility, and hydrogen bonds, as well as clinically relevant anatomic sites. A major void exists in data confirming or denying the completeness of decontamination by measuring absorption and excretion. The development of effective decontamination solutions is of high priority. Abstract : This systematic review summarises experimental studies reporting decontamination with water‐based solutions of dermal chemical contaminants with in vivo human data. Available data show that decontamination with water, soap and water, and 10% isopropanol distilled water is incomplete. Much remains to be learned about decontamination of the large variety of chemical contaminants including a range of molecular weights, lipid and water solubilities, melting points, volatility, and hydrogen bonds, as well as clinically relevant anatomic sites.